ANALISIS EMOTION MARKETING DALAM MENCIPTAKAN POSTPURCHASE BEHAVIOR PADA KAFE KOPI LOKAL DI BANDUNG: Survei pada pelanggan Roemah Kopi dan Ngopi Doeloe - Tiara Emalia, - (2009)
ABSTRACT Tiara Emalia, Emotion Marketing Analysis to Create Postpurchase Behavior in Local Coffee Cafés (Surveying on Roemah Kopi and Ngopi Doeloe customer). It is supervised by Dr. Lili Adi Wibowo, S.Sos.,S.Pd.,MM. and Any Noor, S.Pd., MM. The development of industries of food and beverages market size will full of new comers and it is one of business field which is predicted ordering the extra amount of business with the average rate is 1,6 quintillion per year. One of them is a rest who has specialited in coffee which shows significant development along with the development of cafés that modify the presentation of coffee as beverage. The existence of café is directly indicating on a kind of exclusive life style that then spreading to some cities and also Bandung. There are two player categories in this market of coffee café, the abroad player and local player such as Roemah Kopi and Ngopi Doeloe. The rate of Roemah Kopi and Ngopi Doeloe visit has the same escalation, it is analyzed by marketing emotion strategy which they use, so it influences post purchase behavior. One of the tools that they use in increasing buying experience in both these two local cafés is using Emotion Marketing. Research method which used in this research is explanatory survey because the kind of research is descriptive and verifikatif method, which use proportionate stratified random sampling technique. The technique of data collection which is used is interviewing marketing department of Ngopi Doeloe and Roemah Kopi and questionnaire distribution. The analysis technique that is used is Path Analysis. Based on the result of research on primary hypothesis, it is known that emotion marketing that is consisted of equity value, experience value and energy value has a significant effect on post purchase behavior and the biggest indicator effect is equality value for Ngopi Doeloe and Roemah Kopi café.